Analisis Kritis Citra Perlawanan Wanita Secara Feminis dalam Novel Maryam Karya Okky Madassari - Zulfahreza (Indonesian Journal of Applied Linguistics Review, 2022)
This writing aims to answer the questions in the previous paragraph, the method used by the researcher is a feminist discourse analysis method In this writing, the theory that will be used is the theory of feminism in relation to this novel telling the story of a woman who voiced her rights. In this study the most important problem is how women are displayed and speak in voicing their rights and how the struggle is displayed through the selection of words, sentences and forms of stories to the public. The analysis technique used in this study was the analysis of the Wacana Sara Mills. This method is used in research that focuses on the discourse of women. The point of attentive this method is about how women are displayed in the text. The results of this study concluded that the resistance movement carried out by women could be done through the literary road. By displaying women as a tough main character as a subject who sued the culture of patriarchy who had already been well-established in the community as objects and readers were led to consciously be aware of the mistake that often cornered women.